Gastrointestinal Microbiota Changes in Patients With Gastric Precancerous Lesions - Liu, Dehua; Chen, Si; Gou, Yawen; Yu, Wenyong; Zhou, Hangcheng; Zhang, Rutong; Wang, Jinghao; Ye, Fei; Liu, Yingling; Sun, Baolin; Zhang, Kaiguang (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Gastric microbiota may be involved in gastric cancer. The relationship between gastrointestinal microbes and the risk of gastric cancer is unclear. This study aimed to explore the gastric and intestinal bacteria associated with gastritis and gastric precancerous lesions. Methods: We conducted a case-control study by performing 16S rRNA gene analysis of gastric biopsies, juices, and stool samples from 148 cases with gastritis or gastric precancerous lesions from Anhui and neighboring provinces, China. And we validated our findings in public datasets. Results: Analysis of microbial sequences revealed decreased bacterial alpha diversity in gastric bacteria during the progression of gastritis. Helicobacter pylori was the main contributor to the decreased microbial composition and diversity in the gastric mucosa and had little influence on the microbiota of gastric juice and feces. The gastric mucosal genera Gemella, Veillonella, Streptococcus, Actinobacillus, and Haemophilus had the higher degree of centrality across the progression of gastric precancerous lesions. And Acinetobacter may contribute to the occurrence of intraepithelial neoplasia. In addition, microbial model of H. pylori-positive gastric biopsies and feces showed value in the prediction of PLGC. Conclusions: This study identified associations between gastric precancerous lesions and gastric microbiota, as well as the changes in intestinal microbiota, and explored its value in the prediction of PLGC.